El apalancamiento financiero y su relación con la rentabilidad en la Caja Municipal de Ahorro y Credito Maynas S.A. 2017-2023 - Ruiz Rivera, Cesia Keren-Hapuc; Ruiz Torres, Carlos Daniel (Universidad Nacional de la Amazonía Peruana, 2025)
This research aimed to analyze the relationship between financial leverage and profitability in the Caja Municipal de Ahorro y Crédito Maynas S.A. during the period 2017–2023. Using a quantitative approach with a non-experimental, correlational, and longitudinal design, the study was based on quarterly financial data obtained from official sources such as the Superintendency of Banking, Insurance and AFPs (SBS) and the Central Reserve Bank of Peru (BCRP). Spearman’s rank correlation coefficient was applied to determine statistical associations between different measures of leverage (debt/assets, debt/equity, interest coverage) and profitability indicators (ROA, ROE, net margin). The findings revealed positive and statistically significant correlations, validating the general hypothesis: financial leverage has a direct relationship with profitability. These results differ from previous studies conducted in other business sectors, where the relationship was found to be weak or even negative. In the specific case of Caja Maynas, the strategic use of leverage contributed positively to profitability, indicating a favorable financial management approach. The study concludes with practical recommendations and proposals aimed at optimizing this relationship, offering valuable insight for improving decision-making processes regarding financing and capital structure within microfinance institutions.

La presente investigación tuvo como objetivo analizar la relación entre el apalancamiento financiero y la rentabilidad en la Caja Municipal de Ahorro y Crédito Maynas S.A., durante el periodo 2017–2023. Bajo un enfoque cuantitativo, con diseño no experimental, correlacional y longitudinal, se trabajó con datos financieros trimestrales obtenidos de fuentes oficiales como la Superintendencia de Banca, Seguros y AFP (SBS) y el Banco Central de Reserva del Perú (BCRP). Para el análisis se empleó el coeficiente de correlación de Spearman, permitiendo identificar relaciones estadísticas entre diversas métricas de apalancamiento (deuda/activos, deuda/patrimonio, cobertura de intereses) y de rentabilidad (ROA, ROE, margen neto). Los resultados evidenciaron correlaciones positivas y estadísticamente significativas, lo cual valida la hipótesis general del estudio: el apalancamiento financiero tiene una relación directa con la rentabilidad. Estos hallazgos contrastan con investigaciones previas en otros contextos empresariales, donde la relación fue débil o incluso negativa. La investigación concluye que, en el caso específico de la Caja Maynas, el uso estratégico del apalancamiento contribuyó al fortalecimiento de su rentabilidad, evidenciando una gestión financiera favorable. Se sugieren recomendaciones para optimizar esta relación y propuestas que fortalezcan la toma de decisiones en torno al financiamiento y la estructura de capital.
Keywords: Finanzas empresariales; Financiación; Rentabilidad; Cajas de ahorro; https://purl.org/pe-repo/ocde/ford#5.02.04